PENELUSURAN PEMINATAN JURUSAN DI PERGURUAN TINGGI PADA SMA NEGERI 7 MEDAN - Dhita Adriani Rangkuti; Rosmita Sari Siregar; Sufika Sary; Wirda Lilia; Yovie Ernanda (Jurnal Publika Pengabdian Masyarakat, 2019)
At present there are many students who are less interested in continuing to a higher level while these students have high achievements. According to the Minister of Education (2011), "The number of children aged 19-23 years who continue to PT (college) is only 23%, the remaining 77% do not have the opportunity to enter college, they always consider the factors behind them". For example, such as learning achievement factors and motivational factors as well as interest in learning within the students themselves. This is because the students themselves assume that continuing their studies to a higher level does not guarantee a better future. There is also a high interest to continue to a higher level, but these students have less achievements, the cause of students in learning is very lacking. To achieve the above purpose, UNPRI FE lecturers held a mentoring program and traced the learning interest of class XII students regarding the importance of continuing their education to higher education. The results of the socialization found that 80% of the total class XII students of SMAN 7 Medan had a high interest in continuing their education to higher education. The interest is also equipped with sufficient knowledge about what majors to pursue in collegeKeywords : Majors, Students of Senior High School, University